PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA UMKM DEPOT KAYU VANAY SUKSES MANDIRI - Novita, Lisa; Ardiani, Susi; Dwitayanti, Yevi (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2023)
This article discusses the design of a cash sales accounting information system using Microsoft Visual Basic for Application (VBA) for UMKM Depot Kayu Vanay Sukses Mandiri. The purpose of this system is to simplify the recording of cash sales transactions. The data collection methods used in this research involve interviews and observations. The research findings indicate that the company still uses a manual system for recording sales, which involves using regular ledger books. This manual system has the potential for recording errors, incorrect calculations, neglecting record-keeping, and other mistakes. Furthermore, it can hinder timely access to information about sales and inventory levels, affecting decision-making processes. Therefore, the objective of this report is to design a cash sales accounting information system using Microsoft Visual Basic for Applications (VBA). The designed application features a simple and user-friendly interface to facilitate the management of cash sales transactions. Additionally, this application assists users in accessing the necessary data for decision-making and business planning, as well as generating various useful outputs. The results of this article demonstrate that the company has met the technological requirements analysis needed for this system. Thus, it can be concluded that the developed sales accounting information system will assist the management of UMKM Depot Kayu Vanay Sukses Mandiri in managing sales data and providing the necessary information.Keywords : Accounting Information System, Sales, Microsoft Visual Basic for Application (VBA)